ANALISIS PUTUSAN P.N. BATANG N0.19 Pdt/P/2009/PN.Btg. TENTANG PERUBAHAN STATUS HOKUM SETELAH OPERASI PENYESUAIAN KELAMIN - H. Achmad Busro (Faculty of Law, Universitas Diponegoro, 2013)
n attempt to end the suffering of transessexual patient by changes or adjustments sex that has been done by Agus Widodo, from men become women through surgery, then filed an application to change the legal status of women by the name of Nadia llmira Arkadea. This study uses research methods to analyze the normative juridical decision No .. 19 I Pdt IP I 2009 I P.N. Ba tang. Sex adjustment operations conducted after approval with informed consent of the patients there are several requirements established team of doctors. Furthermore, after completion of the operation,then petition for the legal status from men become to women and the petition is granted by the judge.